Entrepreneurial Risk: Jordan Baltimore and Oyster Digital Media - Lawless, Michael W. (Entrepreneurship Theory and Practice, 2012)
As the global economic downturn entered the last quarter of 2009, Jordan Baltimore, a young but experienced entrepreneur, had to consider alternative funding for his start–up company, Oyster Digital Media. He had planned for venture capital to develop his “Oysters”—electronic shelf tags for retail stores. He was ready to launch his business just as funding became scarce and uncertain. Should he continue to try for venture capital? Angel investors or Friends–and–Family were alternatives, but they could involve less money and delay.